PREDICTING THE PROBABILITY OF THE STERNAL WOUND INFECTION IN PATIENTS UNDERGOING CARDIAC SURGERY - G. G. Khubulava; N. N. Shikhverdiev; P. R. Vogt; S. P. Marchenko; V. V. Suvorov (Вестник хирургии имени И.И. Грекова)
objective. The aim of the study is to create the model for predicting the probability of the sternal wound infection in patients undergoing cardiac surgery after heart operations with the use of longitudinal median sternotomy. Material and methods. The results of treatment of 485 cardiosurgical patients were analyzed; these patients were divided into 2 groups. In the 1st group (265 patients), the prophylaxis of sternal infection was carried out according to a standard procedure, the method of «elimination of sternal infection» was applied in the 2nd group (220 patients). The rate of sternal infection was estimated depending on risk factors. The multiple logistic regression was used to create the model for predicting the risk of sternal wound infection. Results. The created model for predicting the risk of sternal wound infection includes the following factors: application of the method of «elimination of sternal infection» (OR=1871.9; p=0.036); diabetes mellitus type 2 (OR=0.207; p=0.022); the risk according to EuroScore Logistic (OR=1.04; p=0.04); the duration of stay in ICU (OR=1.15, p=0.006). Conclusion: The created model for predicting the risk of sternal wound infection in cardiosurgical patients is excellent effective (p=0.036). The proposed technique for the prevention of sternal infection allowed to reduce the incidence of its occurrence in patients from 7.9 to 0.45 %.